A Case Study of Damage Energy Analysis and an Early Warning by Microseismic Monitoring for Large Area Roof Caving in Shallow Depth Seams - Like Wei; Qingxin Qi; Hongyan Li; Bin Zhang; Yongren Wang; Linghai Kong (Shock and Vibration)
Shallow depth coal seams are widely spread in Shendong mining area, which is located in the Northwestern region of China. When working face is advanced out of concentrated coal pillar in upper room and pillar goaf, strong strata behaviors often cause support crushing accidents, and potentially induce large area residual pillars instability and even wind blast disaster. In order to predict the precise time when the accident happens, guaranteeing life-safety of miner, microseismic monitoring system was for the first time applied in shallow coal seam. Based on damage mechanics correlation theory, the damage energy model is established to describe relationship between damage level and cumulative energy of microseismic events. According to microseismic monitoring data of two support crushing accidents, the damage energy model is verified and an effective early warning method of these accidents is proposed. The field application showed that the early warning method had avoided miners suffering from all support crushing accidents in Shigetai coal mine.